The development of cream-mask base composition for androgenetic alopecia prevention and treatment - M. I. Fedorovska (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Aim. Androgenetic Alopecia (AA) treatment nowadays is still a difficult task of dermatology as the range of drugs that affect the pathological link of disease and are safe for prolonged use, is limited.